Prediction of Low-Dose Aspirin-Induced Gastric Toxicity Using Nuclear Magnetic Resonance Spectroscopy-Based Pharmacometabolomics in Rats - Abubakar, Sha'aban; Hadzliana, Zainal; Nor Azlina, Khalil; Fatimatuzzahra', Abd Aziz; Ch'ng, Ewe Seng *; Teh, Chin Hoe; Mustapha, Mohammed; Baharudin, Ibrahim (MDPI, 2022)
Background: Low-dose aspirin (LDA) is the backbone for secondary prevention of coronary artery disease, although limited by gastric toxicity. This study aimed to identify novel metabolites that could predict LDA-induced gastric toxicity using pharmacometabolomics.